Apakah Training and development, Employee empowerment dan juga Performance Appraisal memiliki pengaruh terhadap Employee Competencies ? - Tsamarah Afnan As’ad; Tiarapuspa (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The skills and abilities of individual employees which are employee competencies are also an important component of human resources. Company goals and targets can be efficient if it has adequate human resources. This can be seen by the presence of high employee competencies in the company. To encourage this, companies must also strive to improve good training and development. Data related to a sample of 152 university students in Jakarta, Indonesia who are already working. The data was obtained using a questionnaire which was then tested for validity and reliability as well as a structural equation model (SEM) using SPSS software version 25 and AMOS version 24. The results showed that the positive influence of training and development, employee empowerment and perceived performance appraisal on employee competencies is supported.